Influences of Schneiderian membrane conditions on the early outcomes of osteotome sinus floor elevation technique: a prospective cohort study in the healing period. Issue 9 (18th July 2016) - Qin, Lei; Lin, Sheng‐xiao; Guo, Zheng‐Ze; Zhao, Ningbo; Song, Ying‐Liang; Xie, Chao; Li, De‐Hua
Abstract: Objectives: To radiographically investigate early outcomes of osteotome sinus floor elevation in the healing phase utilizing cone beam computed tomography and evaluate influences of Schneiderian membrane conditions. Material and methods: One hundred patients were consecutively recruited for osteotome sinus floor elevation (OSFE) surgery using deproteinized bone mineral. CBCT was taken prior to ( T 0), immediately post‐operatively ( T 1), and after the healing period ( T 2). Linear and volumetric measurements of the elevated region from T 0 to T 1 were performed for evaluation on computed tomography (CT). Results: Osteotome sinus floor elevation were performed in 100 patients. One implant of each patient was selected. Mean residual bone height (RH) was 7.21 ± 1.12 mm. Mean sinus floor elevation height (SE) was 4.81 ± 0.75 mm. The mean endo‐sinus bone gain after the healing period was 3.25 ± 0.83 mm. Pre‐opterative CBCT scans revealed that 72 patients had a normal sinus membrane in osteotome region, 13 patients presented with flat thickened mucosa and 15 patients with antral pseudocysts. There is no significant difference in sinus mucosa elevation height, bone graft volume and new bone formation in group of Thickening membrane and Antral pseudocysts compared with normal. Conclusions: The radiographical results show that OSFE is a safe and predictable surgical procedure in residual bone height of 7.21 ± 1.12 mm. Mild flat thickening (>2 and <5 mm) and antral pseudocysts in a small size without clinical symptoms may not be contraindications to OSFE surgery.